Preparation method and application of collagen casing powder
By swelling, drying and crushing the aqueous sodium chloride solution on the collagen casing, the problems of collagen casing waste disposal and collagen powder preparation in the prior art are solved, low-cost and high-efficiency preparation of collagen casing powder are achieved, and resource utilization is promoted.
Patent Information
- Application Number
- CN202411823501.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively dispose of the waste material of collagen casings, and the method of preparing collagen powder has problems such as large equipment investment, cumbersome operation, high energy consumption and low yield.
After swelling treatment with sodium chloride aqueous solution, collagen casing powder is prepared by drying and crushing, using a blade rotary shear high-speed crushing mechanism, and a suitable particle size is obtained through sieving.
It has achieved the preparation of collagen casing powder with low equipment investment, low production cost and high preparation efficiency, met the technical requirements as composite material filler, and promoted the resource utilization of collagen casing solid waste.
Smart Images

Figure BDA0005186260890000071 
Figure HDA0005186261040000011 
Figure HDA0005186261040000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food packaging materials, and specifically relates to a method for preparing collagen casing powder by utilizing waste collagen casings, and application thereof. Background Art
[0002] Collagen casing is an edible material for the outer packaging of sausages. It is usually produced from beef split hides through alkali treatment, crushing, acid swelling, homogenization, degassing, extrusion, neutralization, washing and drying. Casing production is a streamlined operation. Due to production abnormalities, process adjustments and new product trials, a large amount of waste casings is inevitably generated. At present, there is no effective disposal method for waste casings. Long-term storage occupies a large area, and after corruption and deterioration, foul-smelling gases and waste liquids are produced, polluting the environment.
[0003] Collagen casings are mainly composed of collagen, oil, water, glycerol and cellulose, among which the collagen content is 40% to 60%. Therefore, the waste casings produced in the production have a high resource utilization value. In recent years, collagen has been widely used in agriculture, tissue engineering, biomedicine, cosmetics, pharmaceuticals and food industries due to its excellent film-forming properties, degradability and biocompatibility. Due to the complexity of the source and uncertainty of the composition of waste casings, and the extraction of pure collagen from waste casings is not only technically complex but also costly, it is an economically feasible technical route to directly prepare waste casings into powder as fillers to manufacture degradable bio-based composite materials.
[0004] The preparation method of collagen powder usually adopts the spray drying method in the public literature, which has large equipment investment, cumbersome operation, high energy consumption and low yield. For example, patent CN202210092531.2 discloses "A method for preparing triple helical collagen by spray drying", which uses animal tendons as raw materials, prepares collagen stock solution by defatting, slicing, disinfection, low-temperature crushing, acid dissolution and enzymatic hydrolysis, and prepares collagen powder by spray drying. The waste collagen casing film has high toughness and poor crushing performance, and the preparation method of waste collagen casing powder is rarely reported in the public literature. Patent CN117619517A discloses "A scrap collagen casing crushing device", which can only crush the scrap collagen casing into flakes of about 1 cm, and its morphology and particle size cannot meet the technical requirements as a composite material filler.
[0005] Therefore, it is necessary to provide a method for preparing waste collagen casing powder, improve the morphology and particle size of waste collagen casing powder, provide technical support for the development of composite materials based on waste collagen casings, and promote the resource utilization of collagen casing solid waste. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present disclosure provides a method for preparing collagen casing powder from collagen casing solid waste, including the steps of cleaning, swelling, drying, crushing and screening the waste casing. The present disclosure uses an ordinary sodium chloride aqueous solution to soak and swell the waste casings and then dries them, and then uses a blade rotary shearing high-speed pulverizer to crush them, and the waste casing powder can be obtained after screening. The method disclosed in the present disclosure has the advantages of low equipment investment, low production cost, and high preparation efficiency. The prepared waste collagen casing powder can be used as a special filler to manufacture bio-based composite materials, providing a low-cost technical approach for resource utilization of collagen casing solid waste.
[0007] In the present disclosure, collagen casings are mainly composed of collagen, oil, water, glycerin and cellulose, among which the collagen content is 40%-60%. Waste collagen casings are a large amount of collagen casing solid waste that is inevitably generated in the production of collagen casings due to production abnormalities, process adjustments and new product trials.
[0008] According to one aspect of the present disclosure, a method for preparing collagen sausage casing powder is provided, the preparation method comprising the following steps:
[0009] (1) subjecting waste collagen casing to swelling treatment;
[0010] (2) Drying and pulverizing the swollen waste collagen casing to obtain the collagen casing powder.
[0011] In some embodiments, in step (1), the waste collagen casing is swollen in an aqueous sodium chloride solution.
[0012] In some embodiments, the concentration of sodium chloride is 0.5-5.1 mol / L, preferably 2-4 mol / L, more preferably 3.3-3.5 mol / L. In some specific embodiments, the concentration of sodium chloride is 0.5 mol / L, 1 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.1 mol / L or any value therebetween.
[0013] In some embodiments, the mass percentage of the waste collagen casing in the sodium chloride aqueous solution is 2-20%, preferably 5-15%, and more preferably 10%-12%. In some specific embodiments, the mass percentage of the waste collagen casing in the sodium chloride aqueous solution is 2%, 4%, 5%, 6%, 8%, 10%, 11%, 12%, 14%, 16%, 18%, 20% or any value therebetween.
[0014] In some embodiments, in step (1), the swelling treatment time is 0.5-5h, preferably 0.5-2h, more preferably 0.8-1.2h. In some specific embodiments, in step (1), the swelling treatment time is 0.5h, 0.6h, 0.8h, 1h, 1.2h, 1.5h, 2h, 2.5h, 3h, 4h, 5h or any value therebetween.
[0015] In some embodiments, the temperature of the swelling treatment is 50-100° C., preferably 60-80° C., more preferably 65-75° C. In some specific embodiments, the temperature of the swelling treatment is 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 75° C., 90° C. or any value therebetween.
[0016] In some embodiments, after the swelling treatment, the swelling ratio ESR of the waste collagen casing is 3-5, preferably 3.8-4.0, wherein the swelling ratio ESR=W s / W d , W s is the mass of collagen casing after swelling; W d is the dry mass of collagen casing before swelling.
[0017] In some embodiments, in step (2), the drying temperature is 60-120° C., preferably 80-90° C. In some specific embodiments, the swelling temperature is 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C. or any value therebetween.
[0018] In some embodiments, the drying time is 5-30 hours, preferably 12-24 hours. In some specific embodiments, in step (1), the drying time is 5 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours or any value therebetween.
[0019] In some embodiments, the drying process is performed in a drying device.
[0020] In some embodiments, the drying equipment includes, but is not limited to, an electric blower oven, a hot air dryer and / or a fluidized bed dryer.
[0021] In some embodiments, in step (2), the pulverizing process is performed in a high-speed pulverizer.
[0022] In some embodiments, the high-speed pulverizer includes, but is not limited to, a blade rotary shearing high-speed pulverizer, etc.
[0023] In some embodiments, the blade rotation speed of the blade rotary shearing high-speed pulverizer is 30000-50000 rpm, preferably 32000 rpm-35000 rpm. In some specific embodiments, the blade rotation speed of the blade rotary shearing high-speed pulverizer is 30000 rpm, 32000 rpm, 35000 rpm, 40000 rpm, 45000 rpm, 50000 rpm or any value therebetween.
[0024] In some embodiments, the load power of the blade rotary shearing high-speed pulverizer is 3-10kw, preferably 4.0-4.5kw. In some embodiments, the load power of the blade rotary shearing high-speed pulverizer is 3kw, 4kw, 4.5kw, 5kw, 6kw, 7kw, 8kw, 9kw, 10kw or any value therebetween.
[0025] In some embodiments, the particle size of the collagen casing powder after the pulverization process ranges from 1 μm to 500 μm.
[0026] In some embodiments, the average particle size of the pulverized collagen casing powder is 80-220 μm, preferably 100-120 μm.
[0027] In some embodiments, the particle size corresponding to the cumulative distribution percentage of the pulverized collagen casing powder reaching 97% is 200-400 μm, preferably 220-260 μm.
[0028] In some embodiments, the collagen casing powder after the pulverization process has a particle size of less than 150 μm in the collagen casing powder that is greater than 5%, preferably greater than 50%.
[0029] In some embodiments, the preparation method further comprises screening the product after the pulverization process.
[0030] In some embodiments, the screening process is performed using a standard sieve of 100-200 meshes.
[0031] In some embodiments, the preparation method comprises the following steps:
[0032] A1) Clean the waste collagen casings and set them aside for later use;
[0033] A2) placing the cleaned waste casings into a sodium chloride aqueous solution with a molar concentration of 3.3-3.5 mol / L, heating to 65° C.-75° C. and soaking for 45-60 minutes for swelling treatment, removing the waste casings and draining the water for later use;
[0034] A3) Place the drained waste casings into a drying device for drying. The drying temperature is 80°C-90°C and the drying time is 15 hours-24 hours;
[0035] A4) putting the dried waste casings into a high-speed grinder for grinding;
[0036] A5) The crushed waste casings are sieved with a standard sieve of specified mesh size. The sieved powder is sealed in a moisture-proof bag for storage. The unsieved powder can be dried again, crushed and sieved.
[0037] According to another aspect of the present disclosure, provided is collagen sausage coating powder obtained by the preparation method described in the present disclosure.
[0038] According to another aspect of the present disclosure, provided is the use of the collagen casing powder obtained by the preparation method described in the present disclosure in a bio-based composite material filler.
[0039] In some embodiments, the bio-based composite material comprises a waste collagen casing based composite material.
[0040] The present invention performs a sodium chloride aqueous solution soaking swelling and drying treatment on the waste collagen casings, and controls the molar concentration, swelling temperature and swelling time of the sodium chloride aqueous solution to effectively improve the crushing performance, and uses a common blade rotary shearing pulverizer to efficiently prepare powder. The waste collagen casing powder prepared by the present invention is granular, and the yield of particles below 150 μm is very high. The morphology and particle size meet the technical requirements for composite material fillers, and have the advantages of low equipment investment, low production cost, and high preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a photo of waste collagen casings being soaked and swollen in a sodium chloride aqueous solution.
[0042] Figure 2 This is a photo of waste collagen casings after being soaked and swollen in a sodium chloride aqueous solution.
[0043] Figure 3 This is a photo of waste collagen casing after swelling and drying.
[0044] Figure 4 This is a photo of waste collagen casings after swelling, drying and crushing.
[0045] Figure 5 The figures are photos of powders prepared from waste collagen casings by the nine preparation methods of Examples 1-9, wherein samples No. 1 to No. 9 correspond to Examples 1 to 9, respectively.
[0046] Figure 6 This is an electron microscope scanning image of the collagen casing powder prepared in Example 1.
[0047] Figure 7 This is a picture of the particle size distribution of the collagen casing powder after 100 mesh sieving after crushing in Example 1.
[0048] Figure 8 This is a picture of the particle size distribution of the collagen casing powder after 100 mesh sieving after crushing in Example 4.
[0049] Fig. 9 This is a picture of the particle size distribution of the collagen casing powder after 100 mesh sieving after crushing in Example 8. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0051] The reagents and / or kits used in the following examples are all commercially available or can be synthesized by known methods.
[0052] The waste collagen casings in the following examples are waste casings produced in the casing production of Guangxi Shenguan Collagen Biological Group Co., Ltd., and the main components are: collagen, oil, water, glycerin and cellulose.
[0053] Example 1
[0054] A1, clean 100g of waste collagen casing and set aside;
[0055] A2, put the cleaned waste casing into 1000mL of sodium chloride aqueous solution with a molar concentration of 3.40mol / L, heat it to 70℃ and soak it for 60 minutes for swelling treatment (see Figure 1 ), remove the waste casings and drain the water for later use (see Figure 2 );
[0056] A3, put the drained waste casing into an electric blast oven for drying (see Figure 3 ). The drying temperature is 85°C and the drying time is 20 hours;
[0057] A4, put the dried waste casings into a blade rotary shearing high-speed pulverizer for pulverization (see Figure 4 ), the blade speed is 32000 rpm and the load power is 4.5kw.
[0058] A5, the crushed waste casings are sieved with a 100-mesh standard sieve. The sieved powder is sealed in a moisture-proof packaging bag for storage. The unsieved powder is dried again in an electric blast oven at a drying temperature of 85°C for 12 hours. After drying, it is crushed and sieved again (see Figure 5 Sample No. 1).
[0059] Example 1 Electron microscope scanning image of collagen casing powder after crushing and sieving is shown in Figure 6 As shown in Figure 2, the morphology of collagen casing powder is granular. Figure 7 As shown, the particle size range is 1μm to 500μm, the average particle size (D[4,3]) is 105.09μm, and the particle size (D97) corresponding to the cumulative distribution percentage reaching 97% is 248.87μm. The percentage of powder with a particle size below 150μm is 84.3%, that is, the 100-mesh screening yield is 84.3%.
[0060] Example 2
[0061] The difference between Example 2 and Example 1 is that the molar concentration of the sodium chloride aqueous solution used for swelling treatment of the waste casing in step A2 is reduced from 3.40 mol / L to 1.70 mol / L. Figure 5 Sample No. 2. The average particle size of the powder (D[4,3]) is 110.24 μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 253.26 μm. The percentage of powder with a particle size below 150 μm is 43.7%, that is, the 100 mesh sieving yield is 43.7%.
[0062] Example 3
[0063] The difference between Example 3 and Example 1 is that the molar concentration of the sodium chloride aqueous solution used for swelling treatment of the waste casing in step A2 is reduced from 3.40 mol / L to 0.85 mol / L. Figure 5 Sample No. 3. The average particle size of the powder (D[4,3]) is 132.06μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 270.05μm. The percentage of powder with a particle size below 150μm is 36.7%, that is, the 100-mesh screening yield is 36.7%.
[0064] Example 4
[0065] The difference between Example 4 and Example 1 is that the swelling treatment time of the waste casing in step A2 is increased from 1 hour to 3 hours. Figure 5 Sample No. 4. Powder particle size distribution is shown in Figure 8As shown, the particle size range is 1μm to 500μm, the average particle size of the powder (D[4,3]) is 205.69μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 390.89μm. The percentage of powder with a particle size below 150μm is 11.3%, that is, the 100-mesh screening yield is 11.3%.
[0066] Example 5
[0067] The difference between Example 5 and Example 1 is that the molar concentration of the sodium chloride aqueous solution used for swelling treatment of the waste casing in step A2 is increased from 3.40 mol / L to 5.10 mol / L. Figure 5 Sample No. 5. The average particle size of the powder (D[4,3]) is 141.14μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 300.56μm. The percentage of powder with a particle size below 150μm is 40.8%, that is, the 100-mesh screening yield is 40.8%.
[0068] Example 6
[0069] The difference between Example 6 and Example 1 is that the swelling treatment time of the waste casing in step A2 is increased from 1 hour to 1.5 hours. Figure 5 Sample No. 6. The average particle size of the powder (D[4,3]) is 143.59 μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 311.15 μm. The percentage of powder with a particle size below 150 μm is 32.2%, that is, the 100 mesh screening yield is 32.2%.
[0070] Example 7
[0071] The difference between Example 7 and Example 1 is that the swelling treatment time of the waste casing in step A2 is reduced from 1 hour to 0.5 hours. Figure 5 Sample No. 7. The average particle size of the powder (D[4,3]) is 143.36μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 286.88μm. The percentage of powder with a particle size below 150μm is 34.6%, that is, the 100-mesh screening yield is 34.6%.
[0072] Example 8
[0073] The difference between Example 8 and Example 1 is that the temperature of the waste casing swelling treatment in step A2 is increased from 70°C to 90°C. Figure 5 Sample No. 8. Powder particle size distribution is shown in Fig. 9As shown, the average particle size of the powder (D[4,3]) is 168.46 μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 311.53 μm. The percentage of powder with a particle size below 150 μm is 8.4%, that is, the 100 mesh screening yield is 8.4%.
[0074] Example 9
[0075] The difference between Example 9 and Example 1 is that the temperature of the waste casing swelling treatment in step A2 is reduced from 70°C to 50°C. Figure 5 Sample No. 9. The average particle size of the powder (D[4,3]) is 140.70 μm, and the particle size corresponding to the cumulative distribution percentage reaching 97% (D97) is 307.87 μm. The percentage of powder with a particle size below 150 μm is 21.5%, that is, the 100 mesh screening yield is 21.5%.
[0076] Performance Testing
[0077] Through the comparative experiment of different swelling preparation methods in Examples 1-9, the specific test results of the swelling rate of the casing and the yield of casing powder are shown in Table 1. The test results show that the molar concentration, immersion temperature and immersion time of the sodium chloride aqueous solution have a significant effect on the swelling rate of the casing and the yield of casing powder. The molar concentration of the sodium chloride aqueous solution is controlled at 3.40 mol / L, the immersion time is 1 hour, the immersion temperature is 70°C, the swelling rate is controlled at 3.92, and a yield of 84.3% can be achieved.
[0078] Table 1
[0079]
[0080] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing collagen casing powder, comprising the following steps: (1) subjecting waste collagen casing to swelling treatment; (2) Drying and pulverizing the swollen waste collagen casing to obtain the collagen casing powder.
2. The preparation method according to claim 1, characterized in that: In step (1), the waste collagen casing is swollen in a sodium chloride aqueous solution; Preferably, the concentration of sodium chloride is 0.5-5.1 mol / L, preferably 2-4 mol / L, more preferably 3.3-3.5 mol / L; Preferably, the mass percentage of the waste collagen casing in the sodium chloride aqueous solution is 2-20%, preferably 5-15%, and more preferably 10%-12%.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the swelling treatment time is 0.5-5h, preferably 0.5-2h, more preferably 0.8-1.2h; and / or The temperature of the swelling treatment is 50-100°C, preferably 60-80°C, more preferably 65-75°C.
4. The preparation method according to any one of claims 1 to 3, characterized in that After the swelling treatment, the swelling rate ESR of the waste collagen casing is 3-5, preferably 3.8-4.0, wherein the swelling rate ESR=W s / W d , W s is the mass of collagen casing after swelling; W d is the dry mass of collagen casing before swelling.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the drying temperature is 60-120°C, preferably 80-90°C; and / or The drying time is 5-30 hours, preferably 12-24 hours; and / or The drying process is carried out in a drying device. Preferably, the drying equipment comprises an electric blast oven, a hot air dryer and / or a fluidized bed dryer.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the pulverization process is carried out in a high-speed pulverizer. Preferably, the high-speed pulverizer comprises a blade rotary shearing type high-speed pulverizer, More preferably, the blade rotation speed of the blade rotary shearing high-speed pulverizer is 30000-50000 rpm, preferably 32000 rpm-35000 rpm; More preferably, the load power of the blade rotary shearing high-speed pulverizer is 3-10kw, preferably 4.0-4.5kw.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The particle size of the collagen casing powder after the pulverization process is in the range of 1 μm to 500 μm. Preferably, the average particle size of the collagen casing powder after the pulverization process is 80-220 μm; Preferably, the particle size corresponding to the cumulative distribution percentage of the pulverized collagen casing powder reaching 97% is 200-400 μm; Preferably, the collagen casing powder with a particle size below 150 μm accounts for more than 5%, preferably more than 50%.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method further comprises screening the product after the pulverization process; Preferably, the screening process is carried out using a standard sieve of 100-200 mesh.
9. The collagen sausage casing powder obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the collagen casing powder obtained by the preparation method according to any one of claims 1 to 8 in bio-based composite material fillers; Preferably, the bio-based composite material comprises a composite material based on waste collagen casings.
Citation Information
Patent Citations
A method for preparing triple-helix collagen by spray drying
CN114106152B
Concentrated swelling of collagen in preparation of edible collagen casing
CA1071013A
Extraction technology of macromolecular collagen protein
CN101628938A
Soluble non-denatured II-type collagen and preparation method thereof
CN111748030A
Scrapped collagen casing crushing device
CN117619517A
Cited By
Preparation method of collagen casing
CN121176492A